2015
DOI: 10.3168/jds.2014-8695
|View full text |Cite
|
Sign up to set email alerts
|

Effects of season and herd milk volume on somatic cell counts of Florida dairy farms

Abstract: Dairy farms in Florida produce less milk and milk with higher somatic cell counts (SCC) in the hot and humid summer. This has consequences for the interpretation of average milk quality. The objectives were to describe the associations of bulk tank SCC (BTSCC) with time of the year and the milk volume per farm. Monthly BTSCC and milk volume records from 84% (in 2012; n=1,308) and 77% (in 2013; n=1,200) of the 130 dairy farms in Florida were used. Data were analyzed separately per year. We calculated arithmetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…(2012) in Thailand and Hashemzadeh and Khalajzadeh (2014) in Iran reported bulk tank SCC > 500 000 cells/ml and about 347 000 cells/ml during 2010–12 and 2006–07 respectively. Moreover, Ferreira and De Vries (2015) observed relatively higher bulk tank SCC in milk from hot humid areas of Florida than in lower temperature areas. Whilst not definitive, these various data do suggest possible negative effects of heat stress (Zucali et al ., 2011; Smith et al ., 2013; Nasr and El-Tarabany, 2017).…”
Section: Heat Stress and Somatic Cell Count (Scc)mentioning
confidence: 97%
“…(2012) in Thailand and Hashemzadeh and Khalajzadeh (2014) in Iran reported bulk tank SCC > 500 000 cells/ml and about 347 000 cells/ml during 2010–12 and 2006–07 respectively. Moreover, Ferreira and De Vries (2015) observed relatively higher bulk tank SCC in milk from hot humid areas of Florida than in lower temperature areas. Whilst not definitive, these various data do suggest possible negative effects of heat stress (Zucali et al ., 2011; Smith et al ., 2013; Nasr and El-Tarabany, 2017).…”
Section: Heat Stress and Somatic Cell Count (Scc)mentioning
confidence: 97%
“…These results are in accordance with some previous observations. Ferreira and Vries (2015) found that Florida dairy farms produce milk with a lower SCC during the period from February to April in comparison to the period from August to October, which is specifically for hot, humid weather. Therefore, these conditions should be taken into consideration in the programs for improving the milk quality.…”
Section: Discussionmentioning
confidence: 93%
“…So the authors of one of the article on the study of the effect of seasonality on the level of milk yields and SCC noted that the lowest level of SCC and the highest yields in the majority of the dairy farms in Florida are observed from February to April. They also called for new programs to improve the quality of milk, which should be focused on the conditions of animals between August and October, because at this time, most farms show a marked increase in SCC in collected milk and a decrease in milk yields [99].…”
Section: Discussionmentioning
confidence: 99%